Psychometric properties of the self-efficacy subscale of the motivated strategies for learning questionnaire (MSLQ) among Chinese undergraduates - Wei, Zhixia; Che Hassan, Norlizah; Hassan, Siti Aishah; Ismail, Normala; Gu, Xiaoxia; Dong, Jingyi (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigated the psychometric properties and measurement invariance of the selfefficacy subscale of the Motivated Strategies for Learning Questionnaire (MSLQ) in a Chinese undergraduate context. The sample comprised 589 undergraduate students (69.4% female; Mage = 19.21 years, SD = 1.06) from Chinese universities. Psychometric analyses revealed robust properties of the self-efficacy subscale. Multi-group confirmatory factor analysis demonstrated strong evidence supporting configural, metric, scalar, and strict measurement invariance across gender groups, validating the scale’s capability to assess academic selfefficacy constructs equivalently among female and male Chinese undergraduate students. Analysis of participants’ responses indicated moderate levels of academic self-efficacy. This validation study provides researchers and educational practitioners in China with a psychometrically sound instrument for assessing academic self-efficacy, thereby enabling more precise and culturally appropriate investigations in this domain. Implications for future research directions and practical applications are discussed.